Roles of anti-neuroinflammation and anti-oxidative Properties of a standardised andrographis paniculata burm.Nees aqueous extract in improving cognition in wistar Rats (embargo) - Sani, Dahiru (2016)
The number of people worldwide with cognitive/memory impairment is projected to double every 20 years to 81 million by 2050. The rapid expansion of the worldwide aged population is expected to greatly increase the number of individuals with cognitive impairment and this will ultimately have a significant impact on the healthcare cost. To date there is no medicine to treat or prevent cognitive impairment. This has led people to resort to taking herbal supplements for improving memory. One good example of a herb that is becoming increasingly popular for memory improvement is Ginkgo biloba. Substantial studies have shown neuroinflammatory processes to contribute to the cascade of events eventually leading to neuronal degeneration and subsequently loss of memory. This present study evaluated the cognition improving potential and neuroprotective effects of a standardised Andrographis paniculata (locally known as “Hempedu Bumi”) aqueous leaf extract (APAE). The cognitive improvement of APAE was assessed in an in vivo model of lipopolysaccharide (LPS)-induced neuro-inflammation in Wistar rats. Subsequently, the neuroprotective properties of APAE and its major phytochemicals (andrographolide (AGP), neoandrographolide (NAG) and 14-deoxy-11,12-didehydro andrographolide (DDAG)) were evaluated using microglial (BV-2) and dopaminergic (N27) cells. In the in vivo pre-treatment study, rats were pre-treated orally with varied doses of APAE (50 – 400 mg/kg) and a standardised Ginkgo biloba (GB, 50 – 200 mg/kg) extract (EGb761, Tanakan TM , as a positive control) for 7 days before exposure to LPS (1 mg/kg, i.p). Cognitive function was evaluated using a 2-day Morris Water Maze (MWM) protocol with slight modification. Compared with the LPS control group, pre-treatment with APAE at the tested doses effectively prevented memory impairment in the rats as demonstrated by significantly decreasing the mean escape latency of the rats in locating the hidden platform and dose-dependently increasing the number of entries into the target quadrant in the probe. A similar effect was displayed by GB. However, at doses of 50 and 100 mg/kg, APAE was superior to the latter. But at 200 mg/kg both agents produced similar effect. It is interesting to note that GB (200 mg/kg) and APAE (200 and 400 mg/kg) exhibited an improved performance compared to the vehicle-treated control. It was found that APAE was better than GB in improving cognition. In the post-LPS treatment study, both the normal and treated groups (APAE and GB) showed a decrease in the escape latency but interestingly, no significant difference was observed in the probe trial except for group treated with the highest dose (APAE, 400 mg/kg). It was also demonstrated that LPS administration caused increased production of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6), oxidative stress markers (reactive oxygen species (ROS), thiobarbituric acid reactive substances (TBARS), cholinesterase (acetylcholinesterase (AChE), butyrylcholinesterase (BChE) activities and decreased antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) activities and depletion of antioxidant glutathione (GSH) level in the hippocampal region of the brain. Pre-treatment with APAE or GB reversed these effects. Neuropathological evaluation additionally revealed LPS-treated animals to show marked infiltration of inflammatory cells (neutrophils, eosinophils), disorientation of pyramidal cell and loss of small pyramidal cells. However, pre-treatment of rats with APAE or GB significantly (P<0.05) attenuated the LPS effects dose-dependently. Furthermore, TNF-α, IL-1β, IL-6 mRNA levels were increased while SOD, CAT and glutathione peroxidase (GPx) mRNA levels were decreased significantly after LPS administration. Rats pretreated with APAE and GB prevented these effects (P<0.05), which suggested pretreatment of APAE prevented brain toxicity by inhibiting neuro-inflammation and oxidative stress. Urine 1H-NMR metabolomics spectra depicted distinct discrimination in urinary metabolite profiles between control and LPS-treated rats with respect to differences in the metabolites (oxoglutarate, creatinine, allantoin, acetate, citrate, taurine, β- xylose and hippurate) associated with oxidative damage induced by LPS. Urinary metabolite profiles of rats pre-treated with APAE (400 mg/kg) or GB (200 mg/kg) prior to LPS induction showed distribution similar to control animals. This further supported the anti-neuroinflammatory effect of these agents. In the in vitro study, conditioned medium (CM) from LPS-activated glial cells (BV- 2) inhibited N-27 viability but the CM from APAE or AGP pre-treated BV-2 cells did not. This suggested that in vitro the agents were exerting a neuroprotective effect. It was also shown that LPS caused increased production of TNF-α, IL-6 and IL-1β as well as ROS, nitric oxide (NO) and TBARS in BV-2 cells. However, pre-treatment of BV-2 cells with APAE or AGP prior to LPS-stimulation significantly inhibited these effects in a dose-dependent manner, suggesting neuroprotective effect via prevention of inflammatory and oxidative stress mediators. The blood-brain barrier study suggested AGP in APAE has good permeation, further supporting APAE’s neuroprotective potential. The current findings indicate that APAE prevented LPSinduced neuroinflammation mediated cognitive impairment via inhibition of production of pro-inflammatory cytokines, oxidative stress mediators, cholinesterase enzyme activity and improving antioxidant enzyme activity to increase neuroplasticity; all of these translated into improved cognition in rats. The neuroprotective potential of APAE and AGP were further supported in vitro by inhibition of microglial activation via decreased generation of pro-inflammatory and oxidative stress markers. This study provides the mechanistic evidence by which APAE exerts its beneficial effects. The outcome serves as a template to establish the anti-inflammatory and anti-oxidative roles of APAE for neuroprotection, which could have benefit in retarding cognitive impairment in a normal population and additionally may have a role in inhibiting the progression or development of certain neurological diseases associated with neuroinflammation and oxidative stress. In addition, data presented in this study suggested that APAE is a superior cognition improving supplement than the existing market leader EGb761 (Tanakan TM),particularly at lower doses (100 and 50 mg/kg).